Barbershop - Teitel, Robert; Tillman, George, 1969-; Brown, Mark.; Scott, Don D.; Todd, Marshall; Story, Tim.; Ice Cube (Musician); Anderson, Anthony, 1970-; Thomas, Sean Patrick, 1970-; Eve (Musician); Garity, Troy, 1973-; Ealy, Michael; et al. ([United States] : MGM Home Entertainment, 2003)
Calvin never wanted to take over the family business, a barbershop on the south side of Chicago. One morning he decides to sell the shop to Lester. Calvin spends the day cutting heads at the shop, and starts to understand the importance of the legacy left to him. Calvin learns to appreciate his barber friends, and discovers that the place where they work is more than just a place to get a haircut. Calvin gradually changes his mind about selling the shop, but it may be too late. grocery store across the street.
Originally produced as a motion picture in 2002.
Director of photography, Tom Priestley ; editor, John Carter ; music, Terence Blanchard ; costume designer, Devon P.F. Patterson ; production designer, Roger Fortune.
Ice Cube, Anthony Anderson, Sean Patrick Thomas, Eve, Troy Garity, Michael Ealy, Leonard Earl Howze, Keith David, Lahmard Tate, Cedric the Entertainer.
MPAA rating: PG-13, for language, sexual content and brief drug references.
Also issued on DVD.
VHS.
Keywords: Barbershops -- Illinois -- Chicago -- Drama; Barbers -- Drama; Feature films; Comedy films; Video recordings for the hearing impaired